2001
DOI: 10.1007/s002490100148
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroalcohol-induced structural changes of proteins: some aspects of cosolvent-protein interactions

Abstract: The conformational transitions of bovine beta-lactoglobulin A and phosphoglycerate kinase from yeast induced by hexafluoroisopropanol (HFIP) and trifluoroethanol (TFE) have been studied by dynamic light scattering and circular dichroism spectroscopy in order to elucidate the potential of fluoroalcohols to bring about structural changes of proteins. Moreover, pure fluoroalcohol-water mixed solvents were investigated to prove the relation between cluster formation and the effects on proteins. The results demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 0 publications
4
86
0
Order By: Relevance
“…In particular, from knowledge of the TFE dependence of the bulk solvent viscosity (25), at the transition concentration we estimate there is at least 40% TFE around Trp, Ϸ4 times the bulk concentration. Previous X-ray and dynamic light scattering experiments (15,32,33) and molecular modeling studies (20) suggest that the maximum for solvent clustering in water cosolvent occurs near 30-40% (vol/ vol) TFE and that the alcohol concentration is approximately twice that of the bulk concentration; in accord with our solvation measurements. However, we are unaware of another study in which the dynamics associated with solvent clustering near the protein surface have been measured.…”
Section: Construction Of Solvation Energy Of Relaxationsupporting
confidence: 80%
See 2 more Smart Citations
“…In particular, from knowledge of the TFE dependence of the bulk solvent viscosity (25), at the transition concentration we estimate there is at least 40% TFE around Trp, Ϸ4 times the bulk concentration. Previous X-ray and dynamic light scattering experiments (15,32,33) and molecular modeling studies (20) suggest that the maximum for solvent clustering in water cosolvent occurs near 30-40% (vol/ vol) TFE and that the alcohol concentration is approximately twice that of the bulk concentration; in accord with our solvation measurements. However, we are unaware of another study in which the dynamics associated with solvent clustering near the protein surface have been measured.…”
Section: Construction Of Solvation Energy Of Relaxationsupporting
confidence: 80%
“…These results indicate TFE and other fluorinated alcohols create a coating around the peptide, expelling water from the peptide surface, and that the density of TFE is Ϸ2 times higher at the surface of the peptide than that of the bulk concentration (20). Fluorinated alcohols such as TFE and hexafluoroisopropanol have also been shown to aggregate appreciably in water-alcohol mixtures (15,32,33). These clusters have been reported to form a maximum size at a concentration of Ϸ40% (vol/vol) of TFE (32,33).…”
Section: Construction Of Solvation Energy Of Relaxationmentioning
confidence: 93%
See 1 more Smart Citation
“…[186] It has been shown that fluoroalcohols result in conformational change of native proteins, [187] and electrospun fibers lack typical 67nm cross-banding of native collagen. [187][188][189][190] Although collagenous bone grafts provide greater bioactivity and biocompatibility with bone tissue, thereby favoring tissue regeneration, [191,192] these biological functions depend on the unique ultrastructural axial periodicity of collagen. [188] Electrospun collagen nanofibers present poor mechanical properties and thermal stability, which result in collagen denature during the electrospinning process.…”
Section: Biomimetic Electrospun Collagen Nanofibresmentioning
confidence: 99%
“…[1,2] NMR spectroscopy, [3] X-ray diffraction, [4] circular dichroism, [5] FTIR spectroscopy [6] and molecular dynamics approaches [7] have enriched our understanding of the mechanism of the fluoroalcohol intervention in peptide binding. A detailed picture of this important process, on the other hand, is still lacking.…”
Section: Introductionmentioning
confidence: 99%